Classifying the Receivable in a Lease Transaction: A Dilemma. - Wyman, Harold E.; Andrews, Wesley T. (The Accounting Review, 1975)
This article discusses the dilemma that exists in the classification of the receivable in a lease transaction. The current portion of the receivable may be thought of as the discounted value of the payment to be received within one year ($83,333), or the amount by which the principal of the receivable will be reduced during the year ($40,188). Combined with scholars Michael L. Fetters and Steven D. Grossman dilemma, the authors note four possible ways to report on the Statement of Financial Position. In all four methods the total receivable is the same ($299,060), but there is a significant difference in the Current Asset section. Methods 1 and 3 treat the lease receivable as if it were comprised of five separate notes with staggered maturities. Methods 2 and 4 treat the lease receivable as though the firm had loaned a single sum, $299,060, and any payments will be applied first to interest, on the outstanding balance, then to reduction of principal. Thus, the payment received at the end of period 1 would be composed of principal of $40,188 and interest of $59,812.